2013
DOI: 10.1074/jbc.m113.495564
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Cleft Closure of the GluA2 Ligand-binding Domain in the Presence of Full and Partial Agonists Revealed by Hydrogen-Deuterium Exchange

Abstract: Background: Glutamate receptors are essential proteins for transmitting information in the CNS. Results: The stability of H-bonds at multiple points within the ligand-binding domain varies with the efficacy of the bound agonist. Conclusion: H-bonds inside and outside of the binding pocket contribute to channel activation and desensitization. Significance: Fine-tuning of glutamate receptor responses is dependent upon electrostatic interactions and H-bonds outside of the binding pocket.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 31 publications
3
26
0
Order By: Relevance
“…For example, mutations that disrupted an inter-lobe hydrogen bond in GluA2 decreased both agonist affinity and efficacy (Robert et al, 2005). NMR data indicated that, compared to partial agonists with high efficacies, those with low efficacies induced a less stable cleft closure of the GluA2 LBD (Ahmed et al, 2013; Maltsev et al, 2008). According to single molecule FRET experiments on the GluA2 LBD in complex with several partial agonists, the fraction of time that the LBD spent in cleft-closed conformations correlated with the extent of channel activation (Ramaswamy et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…For example, mutations that disrupted an inter-lobe hydrogen bond in GluA2 decreased both agonist affinity and efficacy (Robert et al, 2005). NMR data indicated that, compared to partial agonists with high efficacies, those with low efficacies induced a less stable cleft closure of the GluA2 LBD (Ahmed et al, 2013; Maltsev et al, 2008). According to single molecule FRET experiments on the GluA2 LBD in complex with several partial agonists, the fraction of time that the LBD spent in cleft-closed conformations correlated with the extent of channel activation (Ramaswamy et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Such a relationship between agonist-binding domain cleft closure and ion channel activation provides an elegant means of explaining the link between conformational changes at the agonist-binding site and opening of the channel pore (11). Single molecule fluorescence resonance energy transfer (smFRET) experiments as well as NMR show that, in addition to the inherent ability of a ligand to induce cleft closure, the dynamics also play an important role in dictating activation (12)(13)(14)(15)(16)(17).…”
mentioning
confidence: 99%
“…Relatively small ligands can act as GluK2 specific partial agonists, which may arise from the weak link between D1 and D2 of the LBD of this receptor type. A very recent study (Ahmed et al 2013), using hydrogen-deuterium exchange method, supports the view of hydrogen bonding stability being important in distinguishing full and partial agnists at least in GluA2. In that study, stabilisation of the interdomain H-bonds was weaker for partial than for full agonists.…”
Section: Ihb Disruption Enables Categorisation Of Ligands As Full or mentioning
confidence: 76%
“…In addition to crystallisation, the ligand-binding induced cleft-closure has been extensively studied with several other experimental methods, such as radioligand binding ), fluorescence resonance energy transfer , electrophysiology , nuclear magnetic resonance spectroscopy (Ahmed et al 2013), and site-directed mutagenesis (Weston et al 2006). Recently, computational methods, especially MD simulations, have been utilised to improve our knowledge on the iGluR family structure and function.…”
Section: Ligand-binding Domain Structure and Activationmentioning
confidence: 99%